The Effect of Corporate Social Responsibility Disclosures And Financial Information on Abnormal Return (Empirical Study on Food and Beverage Sub-sector Manufacturing Companies Listed on Indonesian Stock Exchange in 2013-2017) - Suroto Suroto; Ch. Asta Nugraha (Media Ekonomi dan Manajemen, 2019)
This study aims to find empirical evidence of the effect of disclosure of corporate social responsibility and financial information proxied by accounting profits and return on assets to abnormal returns in food and beverage sub-sector manufacturing companies. The population in this study are all companies whose shares are consistently incorporated in the food and beverage sub-sector during the study period. The data used is secondary data in the form of annual reports. The statistical test used to test the hypothesis is panel data regression with a random effect model.The results of this study indicate that disclosure of corporate social responsibility has a negative and insignificant effect on abnormal returns, accounting earnings have a negative and insignificant effect on abnormal returns and return on assets have a positive and significant effect on abnormal returns.Keywords: corporate social responsibility, accounting profit, return on assets and abnormal return.